MECHANISM ALIGNING (GATEWAY) BETWEEN OPERATING SYSTEM BASED ON COMPUTER NETWORKS IN UNOCAL - Vera Morina Oktavia Carla; Drs.Ida Ayu Wiastiti, M.KOM Drs.Ida Ayu Wiastiti, M.KOM (Jurnal Sistem Informasi, 1997)
Computer network is a system that allows for the sharing of information among users.Use of operating systems in the network settings is an absolute must. Replacement ofthe network operating system should really consider the possibility of impacts.Aligning is one solution in order to connect two different systems.